Characterization of the mood state of physically active women and its relation to chronological age and body mass index - Lima, Josivaldo de Souza; Matsudo, Sandra Marcela Mahecha; de Araújo, Timóteo Leandro; Matsudo, Victor Keihan Rodrigues (Journal of Health Care, 2016)
Objectives: To associate and compare the mood state to body weight, body mass index (BMI), and age in women who participate in a physical activity program. Methods: Cross-sectional study with a sample of 435 women with an average age of 68.3Â±7.9 years old, participants in a program of physical activities in São Caetano do Sul, Brazil. The sample is part of the Longitudinal Project of Aging and Physical Fitness in São Caetano do Sul. The sample participation time in the program was approximately 8.8Â±8.5 years and all participants attended to the recommendation of physical activity - walk for 30 minutes, at least five days a week - analyzed by the short version of the International Physical Activity Questionnaire. The BMI was used following the classification of the World Health Organization. The sample was subdivided by age decade: 50-59, 60-69, and >70. The Profile of Mood States (POMS) was evaluated through the original questionnaire with 65 items. A comparison analysis was performed between POMS and BMI through the Kruskal Wallis test and association by odds ratio (OR). Results: Regardless of age decade, most of the sample presented overweight, varying from 43% to 50% (p
Keywords: mood; aging; physical activity; body mass index